ONLINE LEARNING AND ENGLISH LANGUAGE DEVELOPMENT - Ergasheva Dilfuzaxon Tolibjon qizi; Mannabova Ozoda Ilxom qizi; Choriyeva Xurshidabonu Komil qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The integration of digital technologies into education has transformed the process of language learning. Online learning has become one of the most effective approaches to English language development by providing learners with flexible access to educational resources, communication opportunities, and interactive learning environments. This article examines the role of online learning in developing English language skills, including listening, speaking, reading, and writing. Furthermore, it discusses the advantages and challenges of online education and explores modern digital tools that facilitate language acquisition. The study concludes that online learning significantly contributes to English language development when supported by effective teaching strategies and learner motivation.